Analisis Keseimbangan Gaya Pada Balok Statis Menggunakan Konsep Matematika Dasar - jadikan kebaikan telaumbanua (CV. SINAR HOWUHOWU, 2026)
Static equilibrium analysis is a fundamental topic in physics that plays an important role in understanding the behavior of objects at rest under the influence of forces. One of the most commonly discussed cases in statics is a beam subjected to various forces. This study aims to analyze the force equilibrium of a static beam using basic mathematical concepts, including algebraic equations and moment calculations. The analysis is based on the conditions of static equilibrium, namely that the sum of forces acting on the beam and the sum of moments about any point are equal to zero. The research method employed is a descriptive-analytical approach, in which force diagrams and mathematical formulations are used to describe and solve equilibrium problems on a static beam. The results show that the application of basic mathematical concepts can effectively determine reaction forces and internal force conditions on the beam accurately and systematically. This study demonstrates that a clear understanding of mathematical fundamentals significantly supports the comprehension of physical concepts in statics, particularly in analyzing force balance on static structures.